Peran Hadis (الطهور شطر الإيمان) sebagai Bentuk Pencegahan Covid-19 di Desa Sampangan Kecematan Kauman Pekalongan - Abi Hurairah; Muasomah (Madani: Jurnal Pengabdian Ilmiah, 2021)
The emergence of the Corona Virus Diseases-19 outbreak encourages the importance of having a clean and healthy lifestyle. Health is the right of every individual to be able to carry out all daily life activities. To be able to live a healthy life, we must have behaviors that are practiced based on awareness as a result of learning that makes a person or family able to help themselves in the field of public health. At the moment what is happening around us is the Covid-19 outbreak. This virus continues to spread to parts of Indonesia and even to remote villages. As a result of the spread of this virus, many people have become victims and even died. Dense activities and increasing material needs make many people forget to behave healthily. Even though this behavior is very important to maintain health to prevent more people from being infected with the Covid-19 virus. For example, small things that are often forgotten include washing hands before eating and so on according to what the government has advised the Indonesian people to do. Health is a blessing from God where all aspects of life can run starting from being healthy. when we are healthy all activities will feel good. So the human need for health is so great that it is necessary to have clean and healthy living patterns and habits in everyday life.